Representation in Online Prostate Cancer Content Lacks Racial and Ethnic Diversity: Implications for Black and Latinx Men. Issue 3 (4th March 2022) - Loeb, Stacy; Borno, Hala T.; Gomez, Scarlett; Ravenell, Joseph; Myrie, Akya; Sanchez Nolasco, Tatiana; Byrne, Nataliya; Cole, Renee; Black, Kristian; Stair, Sabrina; Macaluso, Joseph N.; Walter, Dawn; et al.
Abstract : Purpose: Black men have the highest incidence and mortality from prostate cancer (PCa) and lower quality of life compared to other U.S. racial groups. Additionally, more Latinx men are diagnosed with advanced disease and fewer receive guideline-concordant care. As many men seek medical information online, high-quality information targeting diverse populations may mitigate disparities. We examined racial/ethnic representation and information quality in online PCa content. Materials and Methods: We retrieved 150 websites and 150 videos about "prostate cancer" using the most widely used search engine (Google) and social network (YouTube). We assessed quality of health information, reading level, perceived race/ethnicity of people featured in the content and discussion of racial/ethnic disparities. Results: Among 81 websites and 127 videos featuring people, 37% and 24% had perceived Black representation, and racial/ethnic disparities were discussed in 27% and 17%, respectively. Among 1, 526 people featured, 9% and 1% were perceived as Black and Latinx, respectively. No content with Black or Latinx representation was high quality, understandable, actionable and at the recommended reading level. Conclusions: Black and Latinx adults are underrepresented in online PCa content. Online media have significant potential for public education and combating health disparities. However, most PCa content lacks diversity and is not readily understandable.